Intramedullary rod fixation of fibrous dysplasia without use of bisphosphonates. (October 2013) - Gaski, Greg; Hansen, Dane; Willis, Leisel M.; Bos, Gary D.; Kean, John R.
Abstract: Purpose: Controversy exists regarding approach to treatment of pediatric patients with fibrous dysplasia. Methods: We retrospectively reviewed medical records of seven patients who were treated at our institution for fibrous dysplasia by intramedullary rod fixation without bisphosphonate supplementation. Results: Seven patients with a total of ten fibrous dysplasia lesion sites surgically treated by intramedullary rod fixation were included. Of these ten lesion sites, eight demonstrated pathologic fracture at the time of fixation. Complete fracture healing was observed in all eight sites, with no incidence of recurrent pathologic fractures examined radiographically. There were no major infections or neurologic deficits, and lesions appeared to stabilize. Conclusions: In this series, intramedullary rod fixation proved to be successful in treatment of acute pathologic fracture and incompletely healed fibrous dysplasia lesions. We observed partial resolution of fibrous dysplasia lesions at all ten sites without significant long-term complications. Following treatment, there were no refractures. Level of evidence: Level IV, case series.